Stock Valuation Analysis in Making Investment Decisions Covid-19 Pandemic - Hermawan, Aditya (Indikator: Jurnal Ilmiah Manajemen dan Bisnis, 2022)
This study aims to determine which stock valuation model is the most appropriate and to find the intrinsic value of the stock prices of companies affected by the COVID-19 pandemic, one way to calculate the intrinsic value of shares is using fundamental analysis with the Price to Book Value (PBV) and Dividend Discount methods. Models (DDM). The sample for this study was 28 companies from 11 sectoral indices affected by the covid-19 pandemic in the third quarter of 2021. The sampling technique in this study used purposive sampling. The data used is secondary data. The analysis tool uses SPSS 25 software. The results of the research on making investment decisions are the most appropriate to buy stocks that are undervalued (cheap). An accurate stock valuation model is the Dividend Discounted Model (DDM) based on Paired samples T-Test.